Principles as the Foundation of Islamic Education - Aisyah Putri Asuri; Mutiara Isma Zahira; Rahma Khairani; Suci Latifah Hermawati; Mudiul Hayat Pasaribu (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
This study examines the foundational principles (asas-asas) as the cornerstone of Islamic education in responding to contemporary educational challenges. The urgency of this study arises from the growing imbalance between cognitive achievement and moral formation within modern educational practices. Using a qualitative approach with a library research design, this article analyzes relevant classical and contemporary literature published within the last decade concerning the principles of Islamic education. Data were collected through documentation techniques and analyzed using content analysis to identify the conceptual framework and practical implications of these principles. The findings reveal that Islamic education is fundamentally built upon several interconnected principles, namely the principle of tauhid (theological foundation), moral principle (akhlak), social principle (kemasyarakatan), and the principle of responsibility and trust (amanah). These principles function as philosophical and operational foundations that guide educational objectives, curriculum development, and character formation. The study concludes that strengthening these foundational principles is essential to ensure that Islamic education remains value-oriented, holistic, and relevant in addressing moral and social issues in contemporary society.